Dampak Penggunaan Gadget terhadap Interaksi Sosial Anak di Mayarakat pada Era Digital (Study pada Masyarakat Daerah Yogyakarta) - Habiby, M. Nuril Anwar; Munadia, Munadia; Mutiasari, Dian; Yunus, Cantika Wulandari (Lembaga Yasin AlSys, 2025)
This research is motivated by the use of electronic devices, including smartphones, by the Indonesian population, particularly social media, which reaches 79.9%. Of course, this usage does not only involve parents but also children. This study aims to analyze the impact of gadget use on children's social interactions in society in the digital era, focusing on the community in the Yogyakarta region. The research employs a qualitative Systematic Literature Review (SLR) approach, using observation, in-depth interviews, and is supported by literature studies through SINTA-indexed articles from 2020 to 2025. The research location is in the Yogyakarta area, and fieldwork was conducted from March 2025 to April 2025. The results indicate that children's use of electronic devices affects their social interactions, including children in Yogyakarta. This is due to the fact that many children aged 6–12 mostly use electronic devices only for playing games, watching videos, and other activities, while rarely using them to access or read educational materials or lessons. As a result, antisocial behavior and difficulties in communication may arise due to dependence on electronic devices. Parents, communities, and schools must actively participate in regulating the use of electronic devices. By adopting a holistic approach, we can mitigate negative impacts and support children's social and emotional development. The main conclusion of this study is that children's use of electronic devices affects their social interactions in Yogyakarta, particularly concerning antisocial tendencies and poor communication skills. The implications of this research are expected to serve as a reference for the government, institutions, and parents to pay closer attention to children and make electronic devices a more positively impactful medium, thus requiring supervision and reasonable time limits in their usage.